BET402 – Medical and Urban Entomology (Entomologi Perubatan dan Bandar) - February - March 2022 - PPSKJ, Pusat Pengajian Sains Kajihayat (2022)
First Semester Examination 2021/2022 Academic Session February/March 2022 BET402 – Medical and Urban Entomology (Entomologi Perubatan dan Bandar) Duration : 2 hours (Masa : 2 jam)